InSURgência na Assessoria Jurídica Popular - Diehl, Diego Augusto; Almeida, Ana Lia de; de Góes Junior, José Humberto; Silva, Valéria Fiori da; Sandri, Anna Carolina Lucca; Costa, Alexandre Bernardino; Oliveira, Assis da Costa; Vestena, Carolina Alves; Pazello, Ricardo Prestes; Rampin, Talita Tatiana Dias (InSURgência: revista de direitos e movimentos sociais, 2018)
.